Management of primary molars with irreversible pulpitis employing tampon pulpotomy: Report of three cases with 34‐month mean follow‐up - Asgary, Saeed (Clin Case Rep, 2021)
This study suggests that tampon‐based coronal pulpotomy using a calcium silicate–based biomaterial can be a reliable approach for the treatment of vital primary molars with irreversible pulpitis.